(untitled) (CIPEEX, 2022)
CHILDHOOD CANCER HAS GROWN EXPONENTIALLY WORLDWIDE. PATIENTS AND FAMILY MEMBERS ARE VULNERABLE AND IN NEED OF PALLIATIVE CARE AND, IN VIEW OF THE NEED TO PROMOTE COMPREHENSIVE HEALTH CARE, IT IS IMPORTANT TO KNOW THE VIEWS OF THOSE WHO CARRY OUT AND THOSE WHO EXPERIENCE THIS PROPOSAL. THEREFORE, THE OBJECTIVE OF THIS INTEGRATIVE LITERATURE REVIEW WAS TO ANALYZE THE PERCEPTIONS OF THE MULTIDISCIPLINARY TEAM AND THE PATIENT-PARENT BINOMIAL REGARDING PALLIATIVE CARE IN PEDIATRIC ONCOLOGY. AS A METHODOLOGY, A SEARCH WAS CARRIED OUT IN THE FOLLOWING DATABASES: VIRTUAL HEALTH LIBRARY (BVS), GOOGLE SCHOLAR, CAPES PORTAL AND SCIELO (SCIENTIFIC ELECTRONIC LIBRARY ONLINE), USING THE DESCRIPTORS IN SCIENCE AND HEALTH (DECS) "PALLIATIVE CARE", €ŒONCOLOGY€ AND €ŒPEDIATRICS€. A TOTAL OF 20 ARTICLES PUBLISHED BETWEEN 2016 AND 2022 WERE SELECTED. IN THIS CONTEXT, THE DIFFICULTY FACED BY PROFESSIONALS WAS HIGHLIGHTED, AS THEY NEEDED TO SEPARATE THE EMOTIONAL SIDE FROM THE PROFESSIONAL, BUT IN A WAY THAT HUMANITY WAS NOT LOST. IT IS ALSO NOTED THE FRAGILITY OF THE PATIENT AND THOSE RESPONSIBLE FOR THEM WHEN THEY ARE FACED WITH SPECIALISTS WHO DEAL COLDLY WITH THE SITUATION, DUE TO ITS DAILY ROUTINE. IN THIS WAY, THE RELEVANCE OF A TRAINED AND HUMANIZED TEAM IS PERCEIVED, WHICH IS ABLE TO TREAT THE PATIENT AS A WHOLE, BUT WHICH ALSO RECEIVES SOCIO-EMOTIONAL SUPPORT, IN ORDER TO PRESERVE THEIR OWN MENTAL HEALTH, AND, IT IS PROVEN, THE BENEFITS PERCEIVED BY THE BINOMIAL PATIENT-PARENTS WHO ARE ASSISTED BY PALLIATIVE CARE.